A chaotic image encryption algorithm combining 2D chaotic system and random XOR diffusion. (1st July 2021) - Sun, Jilei
Abstract: In this paper, an associated color chaotic image encryption algorithm is proposed according to a two-dimensional chaotic system and random XOR diffusion. Firstly, the initial value of the 2D-Logistic-Sine-Coupling map (2D-LSCM) is generated by the SHA-256 and the key stream is generated by the 2D-LSCM. The three channels (red, green, blue) of the color image are processed into a matrix. The key stream is used in the color image scrambling phase according to the cyclic shift. Third, do random XOR diffusion according to the mathematical expression of the 2D-LSCM. In this step, nonlinear diffusion is used, and the scrambling is included in the diffusion. Each pixel value of the ciphertext is XORed by three values, which are the key stream, a pixel value of the scrambled image and the position of the pixel value is different from the position of the ciphertext pixel value, and a non-adjacent ciphertext pixel value. Finally, the statistical analysis is used to test the algorithm. Experimental results show that the algorithm not only reduces the correlation between adjacent pixels, but also reduces the correlation between the three channels of a ciphertext. Compared with some classic algorithm, the algorithm proposed in this paper is more secure.